KARAKTERISTIK HIDRODINAMIKA PENGGUNAAN DUAL FOIL NACA 0012 PADA MONOHULL DAN PENTAMARAN DENGAN MENGGUNAKAN SIMULASI CFD - Muhammad Rifqi Nur Ridwan (2023)
Analysis and continuous innovation regarding dual foil systems are constantly evolving. This study aims to compare the advantages of using the NACA 0012 dual foil model (case 3) on both monohull and pentamaran hulls while maintaining the ship's displacement. Computational Fluid Dynamics (CFD) simulation with ANSYS software is employed for hydrodynamic investigation and model calculations. Hydrodynamic analysis is conducted on both hull types, considering total resistance, frictional resistance, wave resistance, viscous resistance, and lift force of the ship. Parametric study variations for the foils include (Lx2 = 2c, Ly = 0.5c); (Lx2 = 2c, Ly = 0.7c); (Lx2 = 2c, Ly = 1c). The average analysis results comparing the variations of the dual foil between the six monohull and pentamaran models indicate that the pentamaran shows a smaller average analysis result for resistance components, approximately 33% lower, and a larger lift force, approximately 42% greater.